The Use of Artificial Intelligence Chat GPT in Scientific Papers According to the Perspective of Intellectual Property Rights - Alpian, Alpian; Fuad, Fokky; Rifai, Anis (Law Development Journal, 2024)
. Students can use ChatGPT to create scientific work because ChatGPT can answer questions in seconds. However, the creation of scientific works cannot avoid the Copyright Law because it relates to the creation of works via ChatGPT. Unfortunately, there has not been much IPR research regarding chatGPT in scientific publications, even though it is important to continue creating original scientific work. On the basis of this explanation, a problem formulation was found about how the legal awareness of students towards the use of Chat-GPT in writing scientific papers related to the application of Copyright. This encourages researchers to conduct studies regarding the use of artificial intelligence chatGPT in scientific work from an IPR perspective. The aim of this research is to determine the legal liability for using AI ChatGPT in the creation of scientific work from an IPR perspective. The research method used is empirical juridical with data collection techniques through copyright law studies and distributing questionnaires to 100 respondents from 7 faculties of University X, Central Java. The research results revealed that 80% of students used ChatGPT to create scientific papers. Respondents may retain copyright if they use ChatGPT data without duplicating and processing it. However, the author will lose copyright if the use of ChatGPT in the creation of scientific work is not in accordance with research ethics as stated in Copyright Law Number 28 of 2014 Article 1 Chapter 1.